Model-Model Kreatif Distribusi Zakat Berbasis Masyarakat - Fauzi Muharom (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2010)
This writing is aimed at exploring the models of zakat distribution that might be most applicable in modern era. This is necessary sine the zakat distribution presently doesn’t meet the persons in need maximally. Besides, the unnecessary impacts of zakat sometimes occur such as creating envy and quarreling among the people. Zakat can be distributed in consumptive and productive models. Consumptive models is a model in which zakat is directly give to the people to consume. In the productive models, zakat is distributed in such a way that zakat not is directly consumed at once but it is given to the people for production activity. Productive models involve In Kind, Revolving Fund (al-qard al-hasan), and mudarabah system. In kind system, zakat is distributed in the forms of production equipments. People use those equipment for productive activities so they can do business for their life. In revolving fund (al-qard al-hasan) system, zakat is given similar the the system in al-qard al- hasan, but and quarreling the profit of the business is shared with the zakat management board.